Pengembangan Agrowisata Buah Belimbing Untuk Peningkatan Ekonomi Masyarakat Kelompok Tani Di Desa Moyoketen, Kecamatan Boyolangu, Kabupaten Tulungagung - Anggoro Putranto (Jurnal INDONESIA RAYA (Pengabdian pada Masyarakat Bidang Sosial, Humaniora, Kesehatan, Ekonomi dan Umum), 2020)
This research discusses the efforts to optimize the management of star fruit agro-tourism in Moyoketen Village, Boyolangu District, Tulungagung Regency. Star fruit agrotourism is expected to be able to contribute to the economic improvement of the village farmer group community. Various efforts have been made by farmer groups to exploit the potential of the region and process raw products. Utilization of the potential of the area includes community coaching on productive land management, processing management, etc. The objectives in this study are (1) to know the community's knowledge and skills in the management of star fruit agro-tourism, (2) to identify the problems faced by farmers and (3) determine the sustainable starfruit agro-tourism policy strategy in Moyoketen Village.This research is a community service based research, data collection techniques with observation, interviews, and documentation and FGD. The research subjects were 25 starfruit farmers. The results of the primary data analysis were carried out by a SWOT analysis. Research Results Farmers' community knowledge about starfruit farming in general is relatively the same, such as packaging starfruit after picking, making organic fertilizer, plant fertilization phase. The problems faced are decreasing the quality of fruit in a certain season, the number of star fruit availability that is not sufficient demand. Strategies that can be taken for sustainable agro-tourism by increasing understanding among group members, collaborating with starfruit peers in one region or outside the region, priority tourist policies, increasing the promotion of agro-tourism, Government policies for tips on exhibiting and developing agro-tourism with the community Keywords: Agro Tourism Development, Star Fruit, Community Economy,